2017
DOI: 10.21608/ejss.2017.550.1073
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and mobility of vanadium in cultivated calcareous soils and some food chain crops

Abstract: RECENTLY, vanadium levels have been increased in soil crust particularly in industrial areas. Vanadium content in food directly depends upon total initial content in soil. The distribution and mobility of vanadium in some calcareous soils along northwestern coastal region of Egypt were studied. The relationship between soil physical and chemical properties and vanadium fractions was studied. The results indicate that the less dominant chemical speciation of vanadium in calcareous soils was soluble and exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…During the growth of some plant species, V is considered fundamental for chlorophyll contents and porphyrin biosynthesis. However, application at high rates of V can reduce plant productivity and retard growth [8,9]. García-Jiménez et al [10] reported that V can regulate the growth and development of pepper plants, even though contrasting effects were found between species and handling circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…During the growth of some plant species, V is considered fundamental for chlorophyll contents and porphyrin biosynthesis. However, application at high rates of V can reduce plant productivity and retard growth [8,9]. García-Jiménez et al [10] reported that V can regulate the growth and development of pepper plants, even though contrasting effects were found between species and handling circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…At high levels of V, the plant's productivity declines. It can be absorbed by plants and regulate their growth and development, although contrasting effects have been reported among species and handling conditions (Taha et al, 2017 andGarcía-Jiménez et al, 2018).There is little published information available on the role of V element in non-biological N-fixation.…”
Section: Introductionmentioning
confidence: 99%